Dysplasia of extraocular muscles presenting as orbital space-occupying lesions–an extremely rare disorder - Tang, Shi-Yu; Han, Meng-Ya; Yan, Jian-Hua (International journal of ophthalmology, 2025)
AIM: To describe the clinical manifestations, imaging features and surgical treatments in 5 cases of extraocular muscle (EOM) dysplasia presenting as orbital space-occupying lesions (SOL). METHODS: Records from the 5 cases with EOM dysplasia between 2004 and 2016 were retrospectively reviewed and clinical data were recorded including family history, age at onset, age at surgery, visual acuity, cycloplegic refraction, ocular alignment and motility, stereoacuity, exophthalmos, anterior segment and fundus, orbital computed tomography (CT) or magnetic resonance imaging (MRI) scan, surgical methods and final outcomes. RESULTS: All 5 cases (1 male, 4 females) were unilateral (3 right, 2 left eyes). The average age was 5.4y (range 4-6y) with no family history. Patients had unilateral strabismus (horizontal and vertical), restricted eye movement, and eyelid changes (abnormal fissures, lagophthalmos, and/or entropion) in the affected eye. None had proptosis; 1 had 2-mm enophthalmos. Orbital CT/MRI showed irregular, ill-defined masses in EOM. Two anterior orbitotomies and 3 strabismus surgeries were performed, and pathology confirmed EOM dysplasia. After surgery, horizontal deviations, which ranged from exotropia (XT) 10 prism diopter (PD) to esotropia (ET) 10 PD (average 6 PD), decreased by an average of 18 PD, while vertical deviations, which ranged from 4 PD to 20 PD (mean 9.8 PD), decreased by an average of 23.2 PD. CONCLUSION: SOL from EOM dysplasia is non-familial and typically presenting unilaterally characterized by an irregular, diffusely infiltrating mass within the EOM. EOM involvement causes strabismus, restricted eye movement, eyelid changes, and enophthalmos likely due to cicatricial processes.